The Effectiveness of Food Vlogger Review on Purchase Intention Toward Food Product (Study on Mega Influencer) - Dewanthi, Desyra Sukma (Bina Nusantara University, 2024)
Objectives: The objective of this research is to investigate the factors, such as source credibility (attractiveness, trustworthiness, and competence) and brand-influence match up congruence, that might contribute to better customer attitudes and buy intentions. The study is focused on millennials and Gen Z between the ages of 18 and 34 who have recently seen food vloggers review products on Youtube. Method: This research utilizes using an online questionnaire that is made with Google Form distributed to 265 respondents. The full-scale data is analyzed through SmartPLS and bootstrapping analysis to test for reliability, validity, and the research’s hypotheses to identify the relationship between variables. Results: The findings of the research shows that trustworthiness, expertise, similarity, liking, and familiarity value has a positive and significant relationship with customer attitude toward food product. Customer attitude toward food product also has a positive and significant relationship with purchase intention. Then both Attractiveness and Brand-Influencer Match-up does not have a positive influence significant effect on customer attitude toward food product. Conclusion: The results of this research, it can be concluded there are 6 variables that measure food vlogger reviews that are included in the source credibility model, namely trustworthiness, attractiveness, expertise, liking, familiarity, and similarity. The more trustworthiness, expertise, similarity, liking, familiarity felt by food vloggers by customers, the more positive customer attitudes towards food products will be. Key words: Youtube, Food vloggers, Food Product, Customer Attitude, Purchase Intention